Association of Hypothyroidism with Infrequent Tension-Type Headache (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Tension-type headache is a common neurological problem among general population of Bangladesh.Objective: This study was undertaken to ascertain the frequency of subclinical and over hypothyroidism in patients with infrequent TTH.Methodology: This study was conducted in a tertiary care hospital Dhaka medical college in Bangladesh. The study subjects consisted of 200 patients primary headache disorders. Thyroid function test were performed. All four sub-types of tension type headache were considered to include in the study, namely: Infrequent episodic (or infrequent), frequent episodic (or frequent), chronic sub-type and probable sub-type.Result: Forty percent (40%) patients in this study had infrequent TTH, 30% had frequent episodic TTH, 21% had chronic sub-type of TTH and 9% patients had probable sub-type of TTH. overt hypothyroidism. Among 46 patients with frequent episodic TTH 10 patients had subclinical hypothyroidism and 4 patients had overt hypothyroidism. Out of 18 patients with probable TTH 3 patients had subclinical hypothyroidism but no patient was overt hypothyroid. Out of 42 chronic TTH patients 12 had subclinical and another 12 had overt hypothyroidism. Statistically significant difference was seen among different sub-types of headache in relation to thyroid status.Conclusion: Hypothyroidism is found to be a co morbidity or precipitating factors to be development of infrequent type of tension-type headache.Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 60-64